Role of brownian motion and thermophoresis effects on hydromagnetic flow of nanofluid over a nonlinearly stretching sheet with slip effects and solar radiation - Anjali Devi, S.P.; Mekala, S. (Zielona Góra: Uniwersytet Zielonogórski)
Hydromagnetic flow of water based nanofluids over a nonlinearly stretching sheet in the presence of velocity slip, temperature jump, magnetic field, nonlinear thermal radiation, thermophoresis and Brownian motion has been studied. The article focuses on Cu water nanofluid and Ag water nanofluid.
Keywords: nanofluid; MHD; radiation; slip flow; stretching sheet